Dynamics of dry tropical forest after three decades of vegetation suppression - Melo,Cybelle Laís Souto Maior Sales de (2019)
ABSTRACT The aim of this study was to analyze the dynamics of the community and shrub-woody individuals in a dry forest in the Brazilian semiarid region after 29 years of vegetation suppression. Individuals with a circumference at 1.30 m above the ground (CBH) ≥ 6 cm were counted and their heights and CBH were measured in 40 permanent plots on three monitoring occasions (2011, 2013 and 2015). In the period between 2011 and 2015 the area presented a below average precipitation for the last 30 years. Phytosociological parameters and diversity were estimated. The density of individuals decreased from 2011 to 2015 (p < 0.01) and the basal area was similar. During the monitoring period, Poincianella bracteosa stood out in density, frequency and dominance. Phytosociological changes were more evident for an interval of four years. After 29 years of vegetation suppression, the community diversity is within the values for preserved semiarid (caatinga) vegetation. A long period of drought was the main disturbance factor affecting vegetation dynamics.